POTENSI AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL DAUN SINGKIL(Premna corymbosa Roxb & Willd.) - Dewi, Camelia Eugenia; Saleh, Chairul; Ryn Pratiwi, Djihan; Magdaleni, Agustina Rahayu; Daniel, Daniel (Jurusan Kimia FMIPA UNMUL, 2024)
Antioxidant and sunscreen activity tests have been carried out on the methanol extract of singkil leaves(Premna corymbosa Roxb & Willd.) in vitro with the 1.1-diphenyl-2-picrylhydrazil (DPPH) radicalscavenging method using a spectrophotometer UV-Vis. This research aims to determine the antioxidantof singkil leaf. Based on the results of the phytochemical test, it is known that the methanol extract ofsingkil leaves contains alkaloids, flavonoids, phenolics, quinone and steroids. The IC50 value ofmethanol extract of singkil leaves, ia 50.77; in the moderate to strong antioxidant category.